The Role of Independent Commissioners in Improving Corporate Financial Performance - Adhinegoro, Muhammad Bagus; Budisusetyo, Sasongko (JEMBA: Journal of Economics, Management, Business and Accounting, 2023)
This study aims to determine the influence of the board of directors, managerial ownership, independent board of commissioners and institutional ownership on company performance. The study population used were food and beverage companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021. The number of samples in this study was 54 samples from 40 companies selected by purposive sampling techniques. Data analysis using descriptive statistical analysis and multiple linear regression test with SPSS application. The results showed that managerial ownership and the board of commissioners had a positive effect on the financial performance of companies in the food and beverage sector. Meanwhile, the board of directors and institutional ownership negatively affect the financial performance of food and beverage sector companies.